Comparative Analysis of Profitability Before and After Using E-Commerce - Azkhiya Permata Julia; Hendratno Hendratno (Program Studi Manajemen, Fakultas Ekonomi, Universitas Langlangbuana, 2020)
The dynamics of people's behavior in shopping are changing and increasingly diverse. Advances in technology encourage each business sector to innovate and adapt to changing needs. The world of buying and selling online or e-Commerce has changed the landscape of the offline retail business. Many of the retail companies turned to e-Commerce. Kawan Lama Retail Group that houses Ace Hardware, one of the large companies which are a pioneer and the most complete home and lifestyle equipment center, continues to innovate and increase the number of sales by providing the customer’s needs with official e-Commerce Ruparupa.com. This study is to determine how significant the difference in profitability is caused by the application of e-Commerce. Based on the increase in profits, this research is associated with the company's profitability ratios including NPM, ROE, and ROA. Data testing conducted in this study is a comparative hypothesis test with statistic parametric (t-Test) and statistic nonparametric (Wilcoxon Test). The results of the statistical analysis of the comparative hypothesis test, the significance value of the difference in NPM, ROE, and ROA values are greater than 0.05. These results explain that the period before and after the implementation of e-Commerce showed no significant difference in profitability.